2021
DOI: 10.1016/j.ijpharm.2021.120534
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin encapsulation in nanostructures for cancer therapy: A 10-year overview

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 146 publications
(139 reference statements)
0
21
0
Order By: Relevance
“…Studies reported that curcumin modulates cellular pathways involved in cancer pathogenesis including NF-kB, MAPK, PTEN, P53 and wnt [ 11 ]. Despite these tempting advantages of curcumin, the poor bioavailability limits its exploitation as a therapeutic compound [ 12 ]. Our team has recently formulated and characterized a nano-based encapsulated curcumin, gemini curcumin (Gemini-Cur), with significant anticancer effects on ovarian, gastric, breast and colorectal cancer [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies reported that curcumin modulates cellular pathways involved in cancer pathogenesis including NF-kB, MAPK, PTEN, P53 and wnt [ 11 ]. Despite these tempting advantages of curcumin, the poor bioavailability limits its exploitation as a therapeutic compound [ 12 ]. Our team has recently formulated and characterized a nano-based encapsulated curcumin, gemini curcumin (Gemini-Cur), with significant anticancer effects on ovarian, gastric, breast and colorectal cancer [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin encapsulation in food-grade biopolymers or colloidal delivery systems can overcome the challenges associated with its application [ 77 , 78 ]. Encapsulation technology can increase the solubility and bioavailability of curcumin ( Figure 3 ), while protecting this compound against hydrolysis, enzymatic action, and conjugation inactivation, among others [ 79 , 80 ].…”
Section: Encapsulation Of Curcumin For Application As a Bioactive Agentmentioning
confidence: 99%
“…Different types of synthetic nanocarriers have been developed to deliver curcumin: lipid-based curcumin formulations (liposomes, solid-liquid nanoparticles, nanostructured lipid carriers) and polymeric-based curcumin formulations (micelles, polymeric nanoparticles, polymeric conjugates) (for review see [ 96 , 107 ]).…”
Section: New Nanodelivery Strategies To Increase Pharmacological Activities Of Curcuminmentioning
confidence: 99%